Bibliometric Analysis of International Scientific Production on Pharmacologic Treatments for SARS-CoV-2/COVID-19 During 2020 - Ruiz-Fresneda, Miguel A.; Jiménez-Contreras, Evaristo; Ruiz-Fresneda, Carlos; Ruiz-Pérez, Rafael (Frontiers in Public Health, 2022)
Background: COVID-19 is causing a grave global health and economic crisis and the fight against the pandemic has led to unprecedented scientific activity. We have conducted a bibliometric analysis of scientific publications on drugs and therapies used to treat COVID-19. Methods: Data source: Web of Science. We gathered data on scientific production relating to drugs used to treat COVID-19. We calculated impact factors and analysed production by institution, country, and journal, visualizing our results in bibliometric networks. Results: In one year, production relating to COVID-19 exceeded 100 000 publications, with over 6500 on Drugs & COVID-19. Research into Hydroxychloroquine and Chloroquine, Remdesivir, Lopinavir and Ritonavir, Tocilizumab and Convalescent plasma is particularly noteworthy. Mean citations/study range from 11.9 to 15.4. Producer institutions fall into three groups: one in the US and centred on Harvard Medical School; another in Europe led by INSERS; and another in China led by Huazhong University of Science and Technology. Production by journal is widespread but the Journal of Medical Virology, International Journal of Antimicrobial Agents and American Journal of Transplantation are noteworthy. Conclusions: The volume of research that is currently under way is comparable to the magnitude of the pandemic itself. Such a high volume of studies is infrequent and the impact they have achieved has no known precedent. The producing countries are those with highest incidence of the pandemic and greatest scientific potential; moreover, inter-agency and international collaboration has reached extraordinarily high levels.